Ведьмин ключ: повести, роман / Глеб Пакулов - Пакулов Глеб Иосифович (Сибириада, 2019)
Экземпляры: СБ (20191209) / Инвентарный номер: 58754 / Цена: 280.00 / Сис.шифр: Р2 / Авт.знак: П 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6